A set of interesting sequoiatones stereoisomers from a wetland soil-derived fungus Talaromyces flavus - Tianyu Sun; Jian Zou; Guodong Chen; Dan Hu; Bin Wu; Xingzhong Liu; Xinsheng Yao; Hao Gao (Elsevier, 2017)
Four interesting sequoiatones stereoisomers (1-4) were isolated from a wetland soil-derived fungus Talaromyces flavus by chiral HPLC. On the basis of comprehensive NMR and mass analyses, their planar structures were elucidated as the same as that of sequoiatone B. Among them, 1 and 3 (or 2 and 4) were a pair of enantiomers, and 1 and 2 (or 3 and 4) were a pair of stereoisomers with epimerization at C-12, which indicated that sequoiatione-type metabolites exist as enantiomers rather than as optically pure compounds in some strains. With the quantum chemical ECD calculations, the absolute configurations of C-8 in 1-4 were determined, which is the first report to establish the absolute configuration of C-8 in sequoiatones. However, the absolute configurations of C-12 in sequoiatones are still unsolved.